Introduction: Antiquity and Modernity of Soviet Marxism - Chehonadskih, Maria; Chukhrov, Keti; Penzin, Alexei (Stasis, 2017)
Fredric Jameson once pointed out that the Marxist tradition is already our Antiquity due to its significance and historical distance. This distance allows us to view it from the outside, and to reinvent Marxism for our own time. The same could be said about the most paradoxical version of this tradition's Soviet Marxism. However, there are particular qualities that single it out from the classical antiquity of Marxist tradition. Even internationally known Soviet works (by Vygotsky, Bakhtin, amongst Вothers) are not perceived as belonging to a unitary theoretical tradition, and are even less associated with Marxism and the heritage of 1917. It may therefore seem that the October Revolution of 1917, although being recognized as the key event of the short twentieth century has not created a universally recognizable and consolidated body of thought. It is, therefore, a difficult task to outline this field, and this is why the current lens of historical distance might be helpful in attempting to grasp both this unity and the richness of its internal differentiations.